Pengalaman Orangtua Selama Anak Dirawat dengan Penyakit Akut dan Kritis: Literature Review - Yayah; Wanda, Dessie (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2021)
Acute and critical illness threats can cause death. Having an acute and critically ill child who is admissionprovides unique experiences for parents. The aim to describe the experiences during which children undergotreatment for acute and critical illnesses. Methods with online data-based searches ScienceDirect, PubMed,and Wiley published in 2016-2020. The keywords used were mother OR parent AND child AND